2011
DOI: 10.1089/omi.2010.0114
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Resveratrol-Induced Effects in the Human Breast Cancer Cell Lines MCF-7 and MDA-MB-231

Abstract: Resveratrol is a naturally occurring anticancer compound present in grapes and wine with antiproliferative properties against breast cancer cells and xenografts. Our objective was to investigate the metabolic alterations that characterize the effects of resveratrol in the human breast cancer cell lines MCF-7 and MDA-MB-231 using high-throughput liquid chromatography-based mass spectrometry. In both cell lines, growth inhibition was dose dependent and accompanied by substantial metabolic changes. For all 21 ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Methods for detaching adherent cells from culture dishes using trypsin have been shown to cause significant metabolite leakage [23,24,25]. Lastly, methods developed for targeted analyses are not suitable for untargeted analyses as they are optimized to extract metabolites from a specific metabolite class (e.g., only polar metabolites) [26,27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…Methods for detaching adherent cells from culture dishes using trypsin have been shown to cause significant metabolite leakage [23,24,25]. Lastly, methods developed for targeted analyses are not suitable for untargeted analyses as they are optimized to extract metabolites from a specific metabolite class (e.g., only polar metabolites) [26,27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…Findings from our lab and others have demonstrated that Rev possesses various beneficial effects on cardiovascular disease, pulmonary disease, and cancers [19, 32-37]. Jager et al verified that Rev increased the production of serotonin, kynurenine and spermidine, and repressed the level of prostaglandin E2 (PGE2) in the human breast cancer cell lines MCF-7 and MDA-mb-231 [38], indicating that Rev might regulate some small molecules acting as potential markers for disease treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds require tricky preanalytical procedures or challenging analytical methods, for example, nitrated amino acids or oxidized nucleotides. Highly sophisticated sample preparation protocols and mass spectrometric assays have been developed for many of these analytes [139,140] but, due to their complexity and limited robustness, they are still far from a routine application in clinical chemistry.…”
Section: Oxidative Stress and Functional Consequencesmentioning
confidence: 99%